Wildlife Authority Revenue sharing Scheme and Women Empowerment; A Case Study of Mghahinga Conservation area Kisoro District, Uganda - Iradunkunda, Sam; Moses, Agaba (American Journal of Humanities and Social Sciences Research, 2022)
Revenue sharing is currently a popular approach to wild life conservation in Uganda; it involves all communities around the national parks of Uganda and was introduced to change attitudes of communities around the national parks. The benefits from these protected areas are supposed to be shared by all communities around these protected. Women as vulnerable group may not be benefiting much due to marginalization while bearing much of the conservation costs. The objectives of the study were: (i) To identify the ways through which women participate in the revenue sharing scheme. (ii) To analyse the challenges women face in the revenue sharing scheme that hinder them from empowerment in revenue sharing. (iii)To identify appropriate strategies for enhancing women‟s empowerment in revenue sharing arrangements. This research therefore was carried out to analyse how the revenue sharing scheme is benefiting women around the protected areas. The overall aim of the study was to examine women empowerment in UWA‟s revenue sharing scheme. This research was carried out to analyze how the revenues sharing scheme is benefiting women around the protected areas. The research design employed in the study was descriptive research design and qualitative and quantitative approaches were used. The sample of the study comprised of seventy two (72) respondents selected from three parishes of Nteko, Nyamatsinda and Rukongi in Kisoro district all adjacent to the park. Data was collected using Questionnaires which were administered to individual house holds and interviews were conducted for key informants.The Findings indicate that women adjacent to protected areas are not empowered in revenue sharing scheme yet the scheme is meant for them. The barriers to empowerment include corruption by local councils and government officials who handle the revenue, political influence, gender bias towards women and lack of involvement in decision making as well as weak revenue sharing policy and other institutions to cater for women as a marginalized group of people in the community. The study recommends that government puts a law to deal with corrupt officials and even empower women to always refuse money in exchange for things agreed in project proposals. The study also recommends that women should be allowed to access some materials for weaving which can be sold to both foreigners and the local population to earn them extra income.